Elevated serum creatinine in the context of HIV – who is the culprit? Over-the-counter supplements vs. antiretrovirals. (December 2020) - Gill, A; Fernando, KA
We present a case of a 53-year-old male living with well-controlled HIV who, as part of routine monitoring, was noted to have an unexpected decline in renal function. His antiretrovirals were switched accordingly. It subsequently transpired that he had recently started taking creatine supplements in order to build muscle mass. He underwent specialist renal review and further investigation with a chromium-labelled scan which revealed his renal function was, in fact, stable. He continues under renal and HIV follow-up. It is now more widely recognised that creatine can affect renal function, and result in difficulty in interpretation of traditional renal blood tests. However, the further investigations that may be undertaken in such settings and HIV treatment considerations are not as widely reported. This case serves as a reminder to ensure over-the-counter and herbal supplements are part of routine questioning in HIV clinics, and outlines the specialist investigations that may be undertaken in cases of apparent renal decline.